Wonder women of science : twelve geniuses who are currently rocking science, technology, and the world - Fletcher, Tiera, 1995-; Rue, Ginger (Candlewick Press, 2021)
Profiles twelve women in STEM fields, and details their early lives, professional careers, and accomplishments. Provides facts about each woman's field of study, and features advice for getting involved in the world of STEM. Includes color photographs and illustrations, a glossary, and additional resources.